2019
DOI: 10.7494/csci.2019.20.4.3373
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for big data classification based on hybrid parallel dimensionality reduction using spark cluster

Abstract: The big data concept has elicited studies on how to accurately and efficiently extract valuable information from such huge dataset. The major problem during big data mining is data dimensionality due to a large number of dimensions in such datasets. This major consequence of high data dimensionality is that it affects the accuracy of machine learning (ML) classifiers; it also results in time wastage due to the presence of several redundant features in the dataset. This problem can be possibly solved using a fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…A suite of multiple-language APIs is also available on the Apache Spark MLlib [117] platform for the evaluation and deployment of a wide range of machine learning techniques. In recent years, several changes have been made to multiple areas of data science solutions [118], [119], and a number of academics have committed attention to the creation of the components of Apache Spark MLlib for big data analytics.…”
Section: Apache Spark Mllib 20mentioning
confidence: 99%
“…A suite of multiple-language APIs is also available on the Apache Spark MLlib [117] platform for the evaluation and deployment of a wide range of machine learning techniques. In recent years, several changes have been made to multiple areas of data science solutions [118], [119], and a number of academics have committed attention to the creation of the components of Apache Spark MLlib for big data analytics.…”
Section: Apache Spark Mllib 20mentioning
confidence: 99%
“…MAC layer used to map the transport channels to physical channels and it performs scheduling functions in eNB every TTI by assigning RBs to mobile subscribers. The scheduler also determines different transmission parameters like transmitted power and modulation/coding scheme (MCS) which pointed to as radio link adaptation [7,[17][18][19][20]. LTE supports various MCS which can be changed per 1 ms subframe based on wireless channel conditions and interference.…”
Section: Explaining Lte Layers and Protocolsmentioning
confidence: 99%
“…Hence, DT performed better in almost all the attacks. Xiang et al [9] suggested a novel linear correlation feature reduction framework. This framework is beneficial in cases of marginally unrelated features which are jointly related to the response.…”
Section: Literature Surveymentioning
confidence: 99%
“…Hence, there is a need to have an established database of attack signatures [7,8]. The MB approach ensures a good detection of well-known network attacks [4,9]. One major problem of the MB approach is that new or unfamiliar attacks may not be detected.…”
Section: Introductionmentioning
confidence: 99%